2014
DOI: 10.1016/j.cell.2014.09.055
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Development following Somatic Cell Nuclear Transfer Impeded by Persisting Histone Methylation

Abstract: SUMMARY Mammalian oocytes can reprogram somatic cells into a totipotent state enabling animal cloning through somatic cell nuclear transfer (SCNT). However, the majority of SCNT embryos fail to develop to term due to undefined reprogramming defects. Here we identify histone H3 lysine 9 trimethylation (H3K9me3) of donor cell genome as a major epigenetic barrier for efficient reprogramming by SCNT. Comparative transcriptome analysis identified reprogramming resistant regions (RRRs) that are expressed normally at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
581
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 412 publications
(614 citation statements)
references
References 47 publications
29
581
3
1
Order By: Relevance
“…However, the improvement of embryonic development could be due to the changes of complicated gene networks, rather than a single gene. For example, in the recent study, it was found that numerous candidate genes expressed differently after regulation of H3K9me3, but most of these genes function were unclear (Matoba et al 2014). So it was great difficulty, if possible, to determine which genes were responsible for the improvement of embryonic development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the improvement of embryonic development could be due to the changes of complicated gene networks, rather than a single gene. For example, in the recent study, it was found that numerous candidate genes expressed differently after regulation of H3K9me3, but most of these genes function were unclear (Matoba et al 2014). So it was great difficulty, if possible, to determine which genes were responsible for the improvement of embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…And more recently, H3K9me3 was identified as a critical epigenetic barrier in SCNT reprogramming. The reprogramming resistant regions (RRRs) that could not be activated in cloned embryos as that in fertilized embryos were enriched for H3K9me3 in donor cells, and its removal by deletion of H3K9me3 methylase in donor cells and by ectopically expressed H3K9me3 demethylase in cloned emryos not only reactivated the majority of RRRs, but greatly improved SCNT efficiency as well (Matoba et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant advancements have been accomplished in mouse SCNT; however, the simplest approach, the treatment with TSA, does not work in large animals, or better (Sangalli et al, 2012). Of the other ones, RNAi-mediated down-regulation of Xist (Matoba et al, 2011) and the depletion of H3K9 methyl-transferases (Matoba et al, 2014), the first one has a sex bias, working only in female cells, while the second is technically challenging, and hardly accomplishable in large animals, where the molecular biology tool are less advanced. …”
Section: Background: Mousementioning
confidence: 99%
“…2ii), also proved to significantly increase the proportion of offspring. The latest reprogramming efficiency, always developed for the mouse, is the depletion of H3K9me3 methylation in somatic cells before nuclear transfer (Matoba et al, 2014). Tri-methylated H3K9 is a epigenomic landmark conferring resistance to nuclear reprogramming, thus, its genome-wipe up through the exogenous expression of H3Kme9 demethylase increases genome accessibility to reprogramming mechanisms, enhancing in turn cloning efficiency (Matoba et al, 2014) (Fig.…”
Section: Background: Mousementioning
confidence: 99%